Vision-based positioning of electric buses for assisted docking to charging stations - Nowak, Tomasz; Nowicki, Michał; Skrzypczyński, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
We present a novel approach to vision-based localization of electric city buses for assisted docking to a charging station. The method assumes that the charging station is a known object, and employs a monocular camera system for positioning upon carefully selected point features detected on the charging station. While the pose is estimated using a geometric method and taking advantage of the known structure of the feature points, the detection of keypoints themselves and the initial recognition of the charging station are accomplished using neural network models.
Keywords: AI transport; localization; monocular vision; deep learning; keypoints; advanced driver assistance system